2012
DOI: 10.1016/j.saa.2012.04.048
|View full text |Cite
|
Sign up to set email alerts
|

A micro-Raman spectroscopic investigation of leukemic U-937 cells treated with Crotalaria agatiflora Schweinf and the isolated compound madurensine

Abstract: In South Africa traditional medicine plays an important role in primary health care and therefore it is very important that the medicinal use of plants is scientifically tested for toxicity and effectiveness. It was established that the ethanolic extract of the leaves of Crotalaria agatiflora, as well as the isolated compound madurensine, is moderately toxic against leukemic U-937 cells. The investigation showed that micro-Raman spectroscopy has great promise to be used for initial screening of samples to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
(45 reference statements)
0
10
0
Order By: Relevance
“…Medicinal plants have long been studied for their effectiveness in treating cancer. Crude extracts of medicinal plants are more potent cytotoxins because of the synergy of the many phytochemicals found in the mixture [24]. The cell death inducer in this investigation was a leaves extract of Plectranthus ciliatus.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Medicinal plants have long been studied for their effectiveness in treating cancer. Crude extracts of medicinal plants are more potent cytotoxins because of the synergy of the many phytochemicals found in the mixture [24]. The cell death inducer in this investigation was a leaves extract of Plectranthus ciliatus.…”
Section: Introductionmentioning
confidence: 97%
“…In a previous study, we found that Raman micro-spectroscopy could be used to pre-screen a plant extract for its anticancer activity against the proliferation of leukemic U-937 cells [24].…”
Section: Introductionmentioning
confidence: 99%
“…CRM imaging was used to follow the different stages of the cell cycle,36 DNA condensation in late stages of apoptosis and also for the assessment of cell viability 37, 38. DNA damage, lipid changes, and protein denaturation were analyzed as a response to drugs and chemicals 39, 40. However, the spatial resolution and sensitivity of CRM are limited compared with TEM which typically has a threshold of ~60 nm 41…”
Section: Label‐free Dosimetry and Imaging Techniques—toward High Thromentioning
confidence: 99%
“…Correction for spectral di®erences due to relative intensity changes was performed by vector normalization. First derivative and vector normalized spectra were interpolated in 800-1800 cm À1 region 16,22,26,28,[31][32][33] and used as input for multivariate analysis by principal component-linear discriminant analysis (PC-LDA). PC-LDA models were then validated by leave-one-out cross-validation (LOOCV).…”
Section: Spectral Pre-processing and Multivariate Analysismentioning
confidence: 99%
“…19 It has the advantage of having minimum interference from water bands which makes it more appropriate for biomedical applications 20 and provides an easy, chemicalfree and nondestructive method for studying cells in vitro, cell drug interactions as well as for distinguishing neoplastic from normal tissues. [21][22][23][24][25][26][27][28][29][30][31][32] Each tumor is composed of several distinct cell populations and thus the potential and e±cacy of chemotherapy is largely governed by the presence of most chemosensitive or rather least resistant cell populations. Identi¯cation of a resistant/sensitive phenotype in cancer cells from the patients can enhance the e±cacy of therapy.…”
Section: Introductionmentioning
confidence: 99%